The Reality of Managing Academic Competencies at Prince Sittam Bin Abdulaziz University - Alkhonain, Hessah Mohammed; Almashal, Nora Hamad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed at identifying the reality of managing academic competencies at Prince Sattam bin Abdulaziz University in its dimensions (competent development, retaining competencies, and job succession) from the academic leaders' perspectives. Also, this study aimed to shed light on the obstacles to managing academic competencies at Prince Sattam bin Abdulaziz University from the academic leaders' views. Additionally, this study has proposed to overcome the obstacles to managing academic competencies, and to show statistically significant differences between the arithmetic averages in the responses of the study sampling regarding the reality of managing academic competencies (competence development, retention of competencies, and job succession) which have been attributed to two variables namely: experience and academic rank. The researcher has adopted the descriptive survey method, and the study sampling consisted of academic leaders at Prince Sattam bin Abdulaziz University (deans, deputies, and heads of departments) who reached 247 leaders in the academic year 1444 AH. The questionnaire was employed as a tool, and the data was processed statistically utilizing a set of statistical methods for social sciences (SPSS). Furthermore, arithmetic means, standard deviations, one-way test of variance, Pearson's correlation coefficient and least square difference test had been employed. When it comes to the study results, the most important of which is that the reality of managing competences at Prince Sattam bin Abdulaziz University from the leadership’s opinions came with an arithmetic mean of (2.76) with a moderate degree, and the results showed that the total participants are consistent with a moderate degree on the obstacles facing the management of academic competencies. There had been prominent obstacles, some of which is the weak incentives to encourage academic competencies. Also, it has been revealed that the whole participants were consistently high with the proposed procedures overcoming the obstacles.
Keywords: academic competency management; Prince Sattam bin Abdulaziz University; Academic leaders